PENGARUH DUKUNGAN SOSIAL ORANGTUA TERHADAP MOTIVASI BERPRESTASI SISWA SMA KRISTEN CITRA BANGSA SELAMA MASA PANDEMI DAN PASCA PANDEMI COVID-19 - Keo, Glorius Deonatus; Saefatu, Meyrlin; Taneo, Dersy Rejoice; Suan, Elidat Benyamin (Institut Agama Kristen Negeri Kupang, 2024)
Since the pandemic until after the Covid-19 pandemic, learning has been carried out online, including at Citra Bangsa Christian High School, but students are required to continue to increase their achievement motivation because of that, social support from parents is needed. The purpose of this study was to see the effect of Parental Social Support on Student Achievement Motivation using the Quantitative method. The sample determined was 209 students using the Taro Yamane formula. The Parental Social Support Scale according to Taylor while the Achievement Motivation according to McCleland. The instrument has met the Valid and Reliable requirements. The prerequisite test also meets the criteria. Hypothesis testing with Regression analysis found a calculated t value> t table (5.426> 1.285) with a significance of 0.00. The effective contribution of the independent variable to the dependent variable is 25%. It can be concluded that Parental Social Support has a significant influence on the Achievement Motivation of Citra Bangsa Kupang Christian High School students when implementing Online learning. It also proves that the higher the Parental Social Support, the higher the student's Achievement Motivation and vice versa, the lower the Parental Social Support, the lower the student's Achievement Motivation.